2006
DOI: 10.1080/13803390590954209
|View full text |Cite
|
Sign up to set email alerts
|

Five-Factor Personality Dimensions, Mood States, and Cognitive Performance in Older Adults

Abstract: In this study we examined the impact of personality traits and negative mood state on performance in several cognitive domains in a sample of 398 elderly community-dwelling individuals. Multiple linear regression analyses were used to examine the variance in cognitive measures explained by state depression and anxiety after controlling for the effects of demographic characteristics and five-factor model personality traits. Personality traits were found to contribute significantly to cognitive function, explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 18 publications
8
67
5
1
Order By: Relevance
“…913 For example, higher Neuroticism has been linked to cognitive impairment or decline, 11,14 while higher Openness and Conscientiousness may be protective against decline. 10,11 Studies have reported similar findings in terms of these personality domains and risk of Alzheimer’s disease (AD), 9,12,13 The relationships between Extraversion, Agreeableness and cognition are less clear with one study reporting a protective role of moderate Extraversion, 14 one study reporting an association between increased Extraversion and worse cognitive functioning, 11 and no studies reporting significant findings for Agreeableness and cognition. 913 …”
Section: Introductionmentioning
confidence: 97%
“…913 For example, higher Neuroticism has been linked to cognitive impairment or decline, 11,14 while higher Openness and Conscientiousness may be protective against decline. 10,11 Studies have reported similar findings in terms of these personality domains and risk of Alzheimer’s disease (AD), 9,12,13 The relationships between Extraversion, Agreeableness and cognition are less clear with one study reporting a protective role of moderate Extraversion, 14 one study reporting an association between increased Extraversion and worse cognitive functioning, 11 and no studies reporting significant findings for Agreeableness and cognition. 913 …”
Section: Introductionmentioning
confidence: 97%
“…Openness indicates intellectual curiosity and a preference for varied experiences [13,16]. It also is thought to have a moderate correlation with education and cognitive function [13,16,21] that have been closely related to participation in health surveys among the elderly [1,5,[6][7][8]. Thus, there may be also an association between openness and participation status in health checkups.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, a significant association between verbal memory, general cognitive ability and openness is reported [6]. Caregivers describe their relatives as being significantly less open, conscientious and extraverted while showing higher levels of neuroticism after developing a memory disorder [7].…”
Section: Introductionmentioning
confidence: 99%